Identification of Root-Secreted Compounds Involved in the Communication Between Cucumber, the Beneficial Bacillus amyloliquefaciens , and the Soil-Borne Pathogen Fusarium oxysporum - Liu, Yunpeng; Chen, Lin; Wu, Gengwei; Feng, Haichao; Zhang, Guishan; Shen, Qirong; Zhang, Ruifu (Molecular plant-microbe interactions, 2017)
Colonization of plant growth–promoting rhizobacteria (PGPR) is critical for exerting their beneficial effects on the plant. Root exudation is a major factor influencing the colonization of both PGPR and soil-borne pathogens within the root system. However, the tripartite interaction of PGPR, plant roots, and soil-borne pathogens is poorly understood. We screened root exudates for signals that mediate tripartite interactions in the rhizosphere. In a split-root system, we found that root colonization of PGPR strain Bacillus amyloliquefaciens SQR9 on cucumber root was significantly enhanced by preinoculation with SQR9 or the soil-borne pathogen Fusarium oxysporum f. sp. cucumerinum, whereas root colonization of F. oxysporum f. sp. cucumerinum was reduced upon preinoculation with SQR9 or F. oxysporum f. sp. cucumerinum. Root exudates from cucumbers preinoculated with SQR9 or F. oxysporum f. sp. cucumerinum were analyzed and 109 compounds were identified. Correlation analysis highlighted eight compounds that significantly correlated with root colonization of SQR9 or F. oxysporum f. sp. cucumerinum. After performing colonization experiments with these chemicals, raffinose and tryptophan were shown to positively affect the root colonization of F. oxysporum f. sp. cucumerinum and SQR9, respectively. These results indicate that cucumber roots colonized by F. oxysporum f. sp. cucumerinum or SQR9 increase root secretion of tryptophan to strengthen further colonization of SQR9. In contrast, these colonized cucumber roots reduce raffinose secretion to inhibit root colonization of F. oxysporum f. sp. cucumerinum.